Austerity by Design; Comment on “Ensuring Global Health Equity in a Post-pandemic Economy” - Indra De Soysa (International Journal of Health Policy and Management, 2023)
Several scholars across many disciplines argue that neoliberal, free-market economic conditions drive inequalities, generating poverty and misery due to unfair austerity, ultimately affecting human health. Professor Labonté’s prescription is that we jettison these policies targeting economic growth and development for generating greater fairness for the world’s poor. This rejoinder argues contrarily that the criticism of neoliberal policies are misplaced, and that degrowth is really “self-imposed austerity,” which will not benefit the poor. This rejoinder scrutinizes some simple stylized fact and assesses the soundness of the broader arguments. The evidence suggests clearly that becoming wealthy and following prudent economic policies is the best path to improving population health, equity, and other progressive outcomes. Badly required growth for the poor comes from free markets and good governance, and equity for the sake of fairness neither results in better health outcomes, nor an improved environment.